Effects of Varying Levels of Soil pH on the Preservation and Appearance of Gallus gallus domesticus - (:unkn) unknown (My University, 2020)
Results from past studies noted that the carnivore digestion process results in the enlargement of foramina and expansion of Haversian canals within bones. However, it is not known whether acid erosion from soil produces similar signatures. Although bones are oftentimes found within soil matrices, some at highly acidic levels, and the time spent therein undoubtedly affects the preservation and appearance of the remains, these taphonomic effects are still poorly understood. Most studies on bone surface modification focused on how soil affects bone, particularly the diagenic processes involved, such as root and insect activity. The processes studied included root activity, insect movement, and geologic processes, while mostly ignoring the effects of the actual soil itself. Studies of soil erosion on bones have mainly focused on gastric erosion from carnivore ingestion, but the effects of acidity from soil pH levels is still a poorly-studied area within archaeology. The present study aimed to help elucidate this process by examining the effects of erosion due to soil acidity in a controlled environment. Gallus gallus domestics bones (n=24) were placed in containers filled with soil, whose pH values ranged from 4.5-12.6 for five weeks. This study has far-reaching implications within the field of anthropology, expanding upon previous comparative work on taphonomic signatures from hominid-modified and gastrically-modified remains recovered from fossil assemblages. The results of this study added to the literature base on the ways in which soil acidity affects the appearance of skeletal remains. Results from this study indicated that soil acidity expanded the grooves for biceps brachii muscle attachment like previously observed expansion of foramina from effects of gastric erosion, thus highlighting the need for further research into this process.
Keywords: Taphonomy; Soil Erosion; Avian Taphonomy